Pengaruh Pengalaman Kerja, Kompetensi, Independensi,Due Professional Caredan Etika Auditor Terhadap Kualitas AuditStudi Empiris Pada Auditor Inspektorat Kabupaten Boyolali dan Surakarta - Fitriani, Fitriani, Dr. Fatchan Achyani,M.Si (2016)
This purpose of this study was to determine the effect of work experience, competence , independence, due professional care and ethics of auditors on audit quality in the Office off the Inspectorate of Boyolali and Surakarta. The data used in this study is primary data in the form of a respondent's answares from questionair data collection. This study used purposive sampling method in the determinastion of the sample and there were 35 samples that meet the criteria. This study used Multiple Linear Regression Analysis for the data analysis techniques, where the results indicate variable auditor competence and ethics significant effect on audit quality. While variable work experience, independence and professional due care had no significant effect on audit quality. Keywords: work experience, competence, independence, due professional care, ethics of auditors and audit quality.